THE DOLL IN THE PAINTINGS OF THE LATE 19TH – EARLY 20TH CENTURIES: HERMENEUTIC ANALYSIS - Bragina, Natalia; Jermolajeva, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The semantics of the doll in painting is not sufficiently investigated in art history and culture studies. The doll is never an accidental or unimportant component of a painting; it reveals deep psychological and symbolic undertones, complicates and concretizes the content of the painting. Each art style deals with this topic in its own way. The aim of the article is to analyse the interpretation of the image of the doll in various styles of painting of the second half of the XIX century – beginning of the XX century: in realistic painting, in symbolism, impressionism, and modernism. The research methods are the analysis of literature, the descriptive method, the hermeneutic method, and the comparative analysis method. The article may be useful for researchers in art and cultural studies, and can be used at school and university courses in the History of Art and Culture.